Quantifying MCPA load pathways at catchment scale using high temporal resolution data. (15th July 2022) - Atcheson, Kevin; Mellander, Per-Erik; Cassidy, Rachel; Cook, Sally; Floyd, Stewart; McRoberts, Colin; Morton, Phoebe A.; Jordan, Phil
Highlights: An enhanced MCPA dataset was captured in a 384km 2 source water river catchment Catchment export loads were separated into storm event and baseflow pathways A very high total sub-annual MCPA export load of 0.22kg km −2 was calculated Seventy two percent of MCPA was estimated in quickflow loads Deeper baseflow MCPA loads over 12% indicated imperfect degradation Abstract: Detection of the agricultural acid herbicide MCPA (2-methyl-4-chlorophenoxyacetic acid) in drinking water source catchments is of growing concern, with economic and environmental implications for water utilities and wider ecosystem services. MCPA is poorly adsorbed to soil and highly mobile in water, but hydrological pathway processes are relatively unknown at the catchment scale and limited by coarse resolution data. This understanding is required to target mitigation measures and to provide a framework to monitor their effectiveness. To address this knowledge gap, this study reports findings from river discharge and synchronous MCPA concentration datasets (continuous 7 hour and with additional hourly sampling during storm events) collected over a 7 month herbicide spraying season. The study was undertaken in a surface (source) water catchment (384 km 2 —of which 154 km 2 is agricultural land use) in the cross-border area of Ireland. Combined into loads, and using two pathway separation techniques, the MCPA data were apportioned into event and baseload components and the former was further separated to quantify a quickflow (QF) and other event pathways. Based on the 7 hourly dataset, 85.2 kg (0.22 kg km −2 by catchment area, or 0.55 kg km −2 by agricultural area) of MCPA was exported from the catchment in 7 months. Of this load, 87.7 % was transported via event flow pathways with 72.0 % transported via surface dominated (QF) pathways. Approximately 12 % of the MCPA load was transported via deep baseflows, indicating a persistence in this delayed pathway, and this was the primary pathway condition monitored in a weekly regulatory sampling programme. However, overall, the data indicated a dominant acute, storm dependent process of incidental MCPA loss during the spraying season. Reducing use and/or implementing extensive surface pathway disconnection measures are the mitigation options with greatest potential, the success of which can only be assessed using high temporal resolution monitoring techniques. Graphical abstract: Image, graphical abstract